MODIFICATION OF FOOD POLYSACCHARIDE GUM ARABIC WITH POLYBASIC CARBOXYLIC ACIDS - Alexander Sergeevich Kazachenko; Kristina Gurova; Yuri Nikolaevich Malyar; Olga Yurievna Fetisova; Svetlana Andreevna Novikova; Anton Aleksandrovich Karacharov (Химия растительного сырья, 2025)
This work investigates the chemical modification of food-grade gum arabic (GA) using various polycarboxylic acids (citric, adipic, succinic, and oxalic) to enhance its functional properties for advanced applications. The esterification reaction was confirmed through a combination of elemental analysis and FTIR spectroscopy, which indicated the successful incorporation of carboxyl and ester groups into the polysaccharide structure. X-ray diffraction analysis revealed a further amorphization of the modified samples, confirming structural changes. Gel permeation chromatography showed a significant increase in the average molecular weight (Mw) and polydispersity of the derivatives, indicating both cross-linking and chain extension reactions. Atomic force microscopy demonstrated the formation of homogeneous, defect-free films consisting of spherical particles agglomerated into a continuous matrix. Thermal analysis (TGA/DSC) revealed modified thermal degradation patterns and showed that the oxalate derivative (GA-OxA) exhibited the highest thermal stability with a residual mass of 80.73% at 500 °C and the maximum activation energy for decomposition (295 kJ/mol). The results demonstrate the successful synthesis of tailored gum arabic derivatives with improved thermal properties and altered solubility, making them promising materials for applications in food packaging, edible coatings, and as carriers for controlled delivery systems.